Minimial clinically important difference values in distal metaphyseal ulnar shortening for ulnar impaction syndrome and assessment of the relationship between level of the osteotomy and bone union time - Mustafa Özcan; Emre Acar; Onur Başçı; Mustafa Hulusi Özkan (Acta Orthopaedica et Traumatologica Turcica, 2024)
Objective: We aimed to define minimal clinically important difference (MCID) values of patient-reported outcome measures (PROMs) for distal metaphyseal ulnar shortening and to assess the relationship between level of the osteotomy and time to bone union.